New Insights into the Assembly of Extracellular Microfibrils from the Analysis of the Fibrillin 1 Mutation in the Tight skin Mouse - Gayraud, Barbara (The Rockefeller University Press, 2000)
The Tight skin (Tsk) mutation is a duplication of the mouse fibrillin 1 (Fbn1) gene that results in a larger (418 kD) than normal (350 kD) protein; Tsk/+ mice display increased connective tissue, bone overgrowth, and lung emphysema. Lung emphysema, bone overgrowth, and vascular complications are the distinctive traits of mice with reduced Fbn1 gene expression and of Marfan syndrome (MFS) patients with heterozygous fibrillin 1 mutations. Although Tsk/+ mice produce equal amounts of the 418- and 350-kD proteins, they exhibit a relatively mild phenotype without the vascular complications that are associated with MFS patients and fibrillin 1–deficient mice. We have used genetic crosses, cell culture assays and Tsk-specific antibodies to reconcile this discrepancy and gain new insights into microfibril assembly. Mice compound heterozygous for the Tsk mutation and hypomorphic Fbn1 alleles displayed both Tsk and MFS traits. Analyses of immunoreactive fibrillin 1 microfibrils using Tsk- and species-specific antibodies revealed that the mutant cell cultures elaborate a less abundant and morphologically different meshwork than control cells. Cocultures of Tsk/Tsk fibroblasts and human WISH cells that do not assemble fibrillin 1 microfibrils, demonstrated that Tsk fibrillin 1 copolymerizes with wild-type fibrillin 1. Additionally, copolymerization of Tsk fibrillin 1 with wild-type fibrillin 1 rescues the abnormal morphology of the Tsk/Tsk aggregates. Therefore, the studies suggest that bone and lung abnormalities of Tsk/+ mice are due to copolymerization of mutant and wild-type molecules into functionally deficient microfibrils. However, vascular complications are not present in these animals because the level of functional microfibrils does not drop below the critical threshold. Indirect in vitro evidence suggests that a potential mechanism for the dominant negative effects of incorporating Tsk fibrillin 1 into microfibrils is increased proteolytic susceptibility conferred by the duplicated Tsk region.